An analysis on the effect of surface morphology, microstructure and hardness of friction stir processed Mg AZ91 - Zuhairah, Zulkfli (2023)
Low density of magnesium-based alloy is one potential as the lightest structural material for light weight-high strength applications for automotive and aerospace. However, the poor deformability of Mg and its alloys limits the application of the thermomechanical approach. Controlling over temperature and deformation rate is hard to achieve. Among the thermomechanical processes, friction stir processing (FSP) offers an easy way to achieve process stability and mechanical properties enhancement by heat treatment which results in the closure of porosity and refined grain size. During this process, heat is generated by the rotation of the FSP processing tool. Few process parameters as rotational and traverse speeds should be controlled to make FSP stay within the defined processing condition. This thesis study aims to investigate the mechanical properties strengthening on Mg AZ91 using FSP. The surface modification was done on Mg alloy, namely FSPed Mg AZ91 using H13 tool steel with a straight cylindrical pin tool. In this research, each FSP were performed at single pass using different rotational speeds which were 1000, 1100, 1200, 1300 and 1400 rpm while traverse speeds were varied at 25, 35, 45 and 55 mm/min. FSP was used as an approach to refine the microstructure and enhance the mechanical properties of Mg AZ91. Microstructure were observed using optical microscope to reveal the refined grain size within the FSPed specimens. The mechanical properties of Mg AZ91 particularly the hardness was tested and compared. The microstructure after FSP consists of smaller grains as well as the hardness were enhanced about 22 - 65% when compared to base metal Mg AZ91. When FSP rotational speed increases, the average microhardness value increases as the grain size reduces. This significance was due to grain refinement of Mg AZ91. By implementing the material modifications and direct procedure of FSP, the mechanical surface strengthening processes on hardness and microstructure can be boosted. As the result, the optimized parameter to process Mg AZ91 is by using rotational speed: 1400 rpm and traverse speed: 45 mm/min as it has minimum defects observed on the FSPed specimen, consisting the smallest grain of 59.2 μm and fine recrystallized equiaxed grains with highest hardness of 84.4 HV.